Sums of One Prime Power and Four Prime Cubes in Short Intervals - Gen Li; Xianjiu Huang; Xiaoming Pan; Li Yang (Journal of Mathematics)
Let k⩾1 be an integer. In this study, we derive an asymptotic formula for the average number of representations of integers n=p1k+p23+p33+p43+p53 in short intervals, where p1,p2,p3,p4,p5 are prime numbers.